THE INFLUENCE OF PERSON ORGANISATION FIT ON EMPLOYEE PERFORMANCE AT THE CENTRAL CITY SUB-DISTRICT OFFICE GORONTALO CITY - Prahara, Sandi; Ariawan, Ariawan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
This study aims to determine the person organisation fit including value congruence, goal congruence, needs fulfilment, personality culture characteristic congruence simultaneously or partially on employee performance at the Central City District Office of Gorontalo City. The population in this study were all employees as many as 34 people, the main data collection through a list of questions that were tested through two stages, namely validity test and reliability test for each question item contained in the questionnaire. The analysis method used is path analysis. The results showed that, Person organisation fit includes value compatibility, goal compatibility, fulfilment of needs, personality culture characteristics compatibility has a positive and significant effect simultaneously or partially on employee performance at the Central City District Office of Gorontalo City.